2002
DOI: 10.1210/jc.2001-011969
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Thrombin and Hypoxia on Endometrial Stromal and Glandular Epithelial Cell Vascular Endothelial Growth Factor Expression

Abstract: Ovarian steroids and/or premenstrual endometrial hypoxia are thought to restore the endometrial vasculature shed during menstruation by elevating endometrial vascular endothelial growth factor (VEGF) levels. During the luteal phase, VEGF levels peak, progesterone induces estradiol (E(2))-primed human endometrial stromal cells (HESCs) to decidualize and express tissue factor (TF), and endometrial vascular permeability is enhanced. The latter would present circulating clotting factors to decidual cell-expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 80 publications
1
30
2
Order By: Relevance
“…We found that hypoxia markedly enhanced VEGF synthesis in primary cultures of both glandular epithelial and stromal cells. Consistent with the absence of estrogen and progestin response elements from the VEGF gene promoter,27 the VEGF output by glandular epithelial or stromal cells was unaffected by incubation of glandular epithelial or stromal cell with E 2 , a progestin, or E 2 plus progestin either under normoxia or under hypoxia 36. Hypoxia-induced VEGF expression is a putative regulator of an initial wave of angiogenesis, which occurs in the perimenstrual period prior to the elevation in circulating E 2 levels and involves early follicular phase repair of endometrial vessels 37…”
Section: Decidualized Hesc-expressed Tf Promotes Angiogenic Restoratimentioning
confidence: 68%
“…We found that hypoxia markedly enhanced VEGF synthesis in primary cultures of both glandular epithelial and stromal cells. Consistent with the absence of estrogen and progestin response elements from the VEGF gene promoter,27 the VEGF output by glandular epithelial or stromal cells was unaffected by incubation of glandular epithelial or stromal cell with E 2 , a progestin, or E 2 plus progestin either under normoxia or under hypoxia 36. Hypoxia-induced VEGF expression is a putative regulator of an initial wave of angiogenesis, which occurs in the perimenstrual period prior to the elevation in circulating E 2 levels and involves early follicular phase repair of endometrial vessels 37…”
Section: Decidualized Hesc-expressed Tf Promotes Angiogenic Restoratimentioning
confidence: 68%
“…In several studies, VEGFA mRNA and protein expression is increased in endometrial cells in response to oestradiol17b (E 2 ) treatment (Charnock-Jones et al 1993, Shifren et al 1996, Huang et al 1998, Classen-Linke et al 2000. In contrast, other studies report no effect of E 2 or progesterone treatment on endometrial epithelial or stromal cell VEGFA expression (Sharkey et al 2000, Lockwood et al 2002.…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 92%
“…In artificially-cycling macaques, VEGFA mRNA was upregulated in the glands and stroma of superficial endometrial tissues 1-2 days following progesterone withdrawal (Nayak & Brenner 2002). VEGFA expression and secretion is also increased in endometrial epithelial and stromal cells exposed to hypoxic conditions in vitro (Popovici et al 1999, Sharkey et al 2000, Lockwood et al 2002.…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 98%
“…Significantly higher CSPG4 immunostaining in stromal cells and intense superficial microvascular endothelial staining in the endometrium from women post-vs. pre-DMPA use complements our in later angiogenesis stages. Previously, we observed reciprocal thrombin-enhanced secretion of vascular endothelial growth factor (VEGF) [37] and inhibited secretion of angiopoietin (Ang)-1, a blood vessel stabilizing and maturing agent, derived from HESCs [38] as well as increased expression of Ang-2, a proangiogenic vessel-branching and permeability factor, derived from HEECs [39]. Extending these proangiogenic effects, the current study demonstrates that thrombin directly disrupts in vitro HEEC tube formation, branches and meshwork.…”
Section: Page | 11mentioning
confidence: 98%